Reforms in medical education: lessons learnt from Kyrgyzstan. Issue 1 (1st January 2021) - Orozalieva, Gulzat; Loutan, Louis; Azimova, Aigul; Baroffio, Anne; Heller, Olivia; Lab, Bruno; Mambetova, Altynai; Mambetalieva, Damira; Muratalieva, Elvira; Nendaz, Mathieu; Savoldelli, Georges; Vu, Nu V.; et al.
ABSTRACT: Human resources are one of the six building blocks of a health system. In order to ensure that these resources are adequately trained to meet the evolving needs of populations, medical education reforms are needed. In Kyrgyzstan, like in many other low- and middle-income countries, human resources for health are a key challenge for the health system in both the quantity and having their training aligned with the health system priorities. Here we present the experience of the Medical Education Reform Project, a project aimed at improving the quality of health professionals through reforming medical education, funded by the Swiss Agency for Development and Cooperation, as a collaborative effort between partners in Kyrgyzstan and Switzerland since 2013. We used a qualitative study taking a cooperative inquiry approach with an experiential perspective in order to present the implementation of the Medical Education Reform Project in Kyrgyzstan. In order to look at the different components impacting the reform process, a framework comprising: Setting the direction; Building a consensus; Engaging stakeholders; Pilot projects and evaluation; Capacity building; Timing, and Key partners was used to disentangle the lessons learnt. Champions and partnering with key institutions were essential in building consensus, as was the catalytic and facilitating role the project played. This enabled active engagement of a variety of stakeholders in the reform process using different means of interaction ranging from large roundtable discussions, workshops, trainings and even study tours. Pilot projects and research provided tangible actions that could be used to further the reforms. For capacity building, the project offered a wide range of activities that improved clinical competencies, empowered stakeholders, and strengthened organizational capacity. The timing of this reform process in medical education was facilitated by the overall reforms and policies in the health system.